Analysis of temperature dependence of linearity for SiGe HBTs in the avalanche region using Volterra series. (May 2016) - Lee, Chie-In; Lin, Yan-Ting; Lin, Wei-Cheng
Abstract: In this paper, linearity characteristic of silicon germanium (SiGe) heterojunction bipolar transistors (HBTs) at different temperatures in the avalanche regime is investigated by the Volterra approach incorporating with a physics-based breakdown network for the first time. Third-order intermodulation distortion (IMD3 ) decreases with increasing temperature in the impact ionization region due to lower nonlinear contributions from individual nonlinearity according to the Volterra analysis results. Calculated gain, output power, and efficiency of SiGe HBTs are in good agreement with measurement results in the avalanche region. This analysis with respect to temperature can benefit the reliability study of linearity for SiGe HBTs in the avalanche regime. Graphical abstract: Highlights: Linearity of SiGe HBTs at different temperatures in the breakdown region is examined. Lower IM3 at elevated temperature is due to lower nonlinear contributions from each nonlinearity. RF multiplication factor at different temperatures is verified by dead space theory. This analysis can benefit SiGe PA designs at breakdown with reliability considered.